2016
DOI: 10.2196/jmir.5191
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Patients’ Walking Activity Determined by a Step Counter in Cardiac Telerehabilitation: Data From the Intervention Arm of a Randomized Controlled Trial

Abstract: BackgroundWalking represents a large part of daily physical activity. It reduces both overall and cardiovascular diseases and mortality and is suitable for cardiac patients. A step counter measures walking activity and might be a motivational tool to increase and maintain physical activity. There is a lack of knowledge about both cardiac patients’ adherence to step counter use in a cardiac telerehabilitation program and how many steps cardiac patients walk up to 1 year after a cardiac event.ObjectiveThe purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 49 publications
(86 reference statements)
5
61
2
4
Order By: Relevance
“…This study shows that of the 711 initial participants, approximately 50% still used their tracker after 6 months, and 12% continued to use their tracker even after 300 days. This rate of decay in usage confirms earlier findings [18]. This result also confirms the notion that wearable activity trackers are not subject to the rapid exponential decay of use we see in mobile phone apps, where usually 80% of users drop out in the first few days (eg, in [70]).…”
Section: Discussionsupporting
confidence: 89%
“…This study shows that of the 711 initial participants, approximately 50% still used their tracker after 6 months, and 12% continued to use their tracker even after 300 days. This rate of decay in usage confirms earlier findings [18]. This result also confirms the notion that wearable activity trackers are not subject to the rapid exponential decay of use we see in mobile phone apps, where usually 80% of users drop out in the first few days (eg, in [70]).…”
Section: Discussionsupporting
confidence: 89%
“…Meanwhile, better health-related quality of life and exercise capacity, less unplanned clinic visits, and cardiac-caused hospitalization were observed among patients in the regular PA group, compared with the irregular PA group ( P < .05). Substantial research has shown that walking (mild PA) can improve quality of life 25 and exercise capacity 26 among patients with CHD and decrease mortality compared with those who are inactive, in both the general population 27 , 28 and patients. 29 , 30 Wasfy and Baggish, 31 in their review of relevant epidemiologic literature on exercise, also found that the least active patients may benefit most from small increments in PA.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to most step counters used in clinical trials, 19,20 smartphones and smartwatches with built-in pedometers allow for more convenient and probably more accurate measurement of daily step count as marker of everyday PA. The observed compliance rate of >80% and mean wear time of 12.71 ± 1.13 h account for the validity of the measured step count.…”
Section: Validity Of Smart Device-based Measurement Of Health Datamentioning
confidence: 99%